PENGARUH KARAKTERISTIK WIRAUSAHA DAN KREATIVITAS TERHADAP KEBERHASILAN UMKM KULINER DI KECAMATAN MEDAN JOHOR - Salsabil Chairunnisyah; Nur'ain Harahap (Bisnis-Net, 2023)
This study aims to determine the influence of entrepreneurial characteristics and creativity on the success of Culinary Umkm in Medan Johor District. The method used in this study uses descriptive methods. Quantitative research method is a research method used to examine certain populations or samples. The population is also not just the amount that exists in the object or subject being studied, but includes all the characteristics or traits possessed by the subject or object. The population of this study is 40 SMEs Kec. Medan Johore. So the sample used in this research is all members of the population of 40 in UMKM in Medan Johor District. The time of the research to be carried out starts from December 2022 to February 2023. Based on the research results it can be seen from the influence of each variable simultaneously that the value of Fcount (5,356 )> Ftable (2.86) then this shows the characteristics of entrepreneurship and creativity have a significant effect on the success of culinary MSMEs in the Johor sub-district.